Implantation du Soutien au comportement positif (SCP) dans les écoles québécoises: Influence des directions d'écoles. (September 2014) - Bissonnette, Steve; St-Georges, Normand
This paper presents a first assessment of the implementation of Positive Behavioural Interventions and Supports (PBIS), translated into French as Soutien au comportement positif (SCP), in elementary and secondary schools in Quebec. The SCP proposes the establishment of a support system in terms of behaviour management throughout the school to create an environment conducive to learning. The results indicate that it is possible to implement SCP with fidelity in elementary and secondary schools in Quebec; however, fidelity of implementation seems to depend on the leadership of school principals.